2022
DOI: 10.1371/journal.pone.0273166
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive fluorescence sensing for assessing microclimate, site and defoliation effects on flavonol dynamics and sugar prediction in Pinot blanc grapes

Abstract: In an era of growing international competition in modern viticulture, the study and implementation of innovative technologies to increase the production of high-quality grapes and wines are of critical importance. In this study, the non-destructive portable sensor Multiplex, based on fluorescence sensing technique, was applied to evaluate grape maturity parameters and flavonol content of the understudied Pinot blanc variety. The effects of environmental and agronomical factors on flavonol content of Pinot blan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
1
1
0
Order By: Relevance
“…Overall, the field microclimate observation data more accurately reflected the characteristics of the vineyard microclimate than the national reference station data. This result is consistent with a previous study that listed the temperature variation characteristics between a microclimate station and a weather station and concluded that microclimate station data could better represent vineyard climate [11,[20][21][22][23][24][25].…”
Section: Climate Quality For Wine Grape In 2019 and 2020supporting
confidence: 92%
“…Overall, the field microclimate observation data more accurately reflected the characteristics of the vineyard microclimate than the national reference station data. This result is consistent with a previous study that listed the temperature variation characteristics between a microclimate station and a weather station and concluded that microclimate station data could better represent vineyard climate [11,[20][21][22][23][24][25].…”
Section: Climate Quality For Wine Grape In 2019 and 2020supporting
confidence: 92%
“…Flavonoid synthesis is conditioned by the expression of the enzyme flavanoid 3’5’-hydroxylase in white grape varieties, which limits the synthesis to quercetin, kaempferol and isorhamnetin compared to red grape varieties, where myricetin, laricitrin and syringetin are also synthesised [ 41 ]. Flavonols are yellow pigments that contribute to the colour of white varieties and provide several positive effects on human health due to their antioxidant activity [ 39 , 42 ].…”
Section: Resultsmentioning
confidence: 99%